PARADIGMA HUKUM PROGRESIF DALAM PENGATURAN BISNIS PARIWISATA DI BALI: MENYEIMBANGKAN KEPENTINGAN EKONOMI GLOBAL DENGAN PERLINDUNGAN EKOLOGI DAN BUDAYA LOKAL - I Putu Raditya Sudwika Utama (Yayasan Literasi Sains Indonesia, 2026)
The rapid expansion of the global tourism industry has significantly contributed to Bali’s economic growth, while simultaneously generating complex legal, ecological, and socio-cultural challenges. Tourism-driven development often neglects environmental sustainability, marginalizes indigenous communities, and deepens structural inequality in labor and land control. This article aims to examine how the reformulation of progressive legal theory can balance global economic interests with ecological protection and local cultural preservation in Bali, and to develop a sustainable tourism governance model through the integration of state law, Balinese customary law, and international legal norms. This research employs a normative juridical approach, supported by philosophical and sociological legal analysis. The findings indicate that the prevailing procedural and centralistic legal paradigm fails to adequately address Bali’s socio-cultural realities. Progressive legal theory provides a transformative framework by positioning human values, substantive justice, and local wisdom at the core of legal development and enforcement. Furthermore, the concept of legal pluralism becomes a crucial foundation for building inclusive and sustainable tourism governance. Case studies from Penglipuran Village and Junjungan Traditional Village demonstrate that effective integration of state law, customary law, and international principles can produce community-based tourism models that are equitable, environmentally responsible, and culturally resilient. The study concludes that the sustainability of Bali’s tourism sector can only be achieved through legal reform that strengthens indigenous participation, recognizes customary law as a substantive source of regulation, and fosters continuous dialogue among diverse legal systems within a collaborative and justice-oriented governance framework.